Tralokinumab Effectively Disrupts the IL-13/IL-13Rα1/IL-4Rα Signaling Complex but Not the IL-13/IL-13Rα2 Complex - Maxim A.X. Tollenaere; Christina Mølck; Ian Henderson; Scott Pollack; Philip Addis; Helle Heibroch Petersen; Hanne Norsgaard (Elsevier, 2023)
Tralokinumab, a fully human mAb specifically targeting the IL-13 cytokine, has demonstrated clinical efficacy and safety in patients with moderate-to-severe atopic dermatitis. Tralokinumab binds IL-13 with high affinity, which prevents the interaction of IL-13 with IL-13Rα1 and subsequent signaling. Similarly, tralokinumab-bound IL-13 cannot bind to IL-13Rα2, a proposed decoy receptor that is reported to bind IL-13 with extraordinarily high affinity. It has however not been fully elucidated to what extent tralokinumab interferes with the endogenous regulation of IL-13 through IL-13Rα2. In this mechanistic study, we used biophysical, biochemical, and cellular assays to investigate the effect of tralokinumab on the interaction between IL-13 and IL-13Rα1 and IL-13Rα2, respectively, as well as the effects on IL-13Rα2-mediated IL-13 internalization. We demonstrate that IL-13Rα2 binds IL-13 with exceptionally high affinity and that tralokinumab is unable to displace IL-13 from IL-13Rα2. In contrast to this, tralokinumab is able to disrupt the IL-13/IL-13Rα1 and IL-13Rα1/IL-13/IL-4Rα complex. Furthermore, we demonstrate that whereas the IL-13/tralokinumab complex is unable to bind IL-13Rα2, any IL-13 that is not bound by tralokinumab (i.e., free IL-13) can be bound by IL-13Rα2 and subsequently internalized, regardless of the presence of tralokinumab. In summary, our study indicates that tralokinumab does not interfere with endogenous IL-13Rα2-mediated regulation of free IL-13.